Decentred Geographies: Poetics and Politics of the Avant-garde - Božić Blanuša, Zrinka (Poznańskie Studia Slawistyczne, 2020)
Thanks to the work of Pascale Casanova, Franco Moretti, David Damrosch and many others, over the past two decades, the concept of world literature has once again become the subject of thorough examination within the field of literary studies, especially in relation to cosmopolitanism and globalization. When it comes to the study of individual national literatures and specific regional contexts, as well as to the definition of comparative literature as a discipline, debates regarding its background, its reach and limitations could not be ignored. World literature thus appears as a heterogenous entity – always manifesting in different contexts in different forms – consistently in dialogical exchange with specificities of a particular literature and culture. Instead of discussing the problematic relation between centre and periphery or criticizing the idea of global literary and cultural canon, the avant-garde as an international and global phenomenon that appears even more radically on the so-called periphery is what is of primary interest to me. Therefore, the purpose of this paper is to demonstrate that avant-garde (in its various forms and radical expressions) simultaneously challenges art as an institution and introduces the idea of a decentred geography of world literature.